Reliability and Validity of the Y-balance Test in Young Adults with Chronic Low Back Pain - Yousef Alshehre; Khalid Alkhathami; Kelli Brizzolara; Mark Weber; Sharon Wang-Price (North American Sports Medicine Institute, 2021)
# Background Individuals with chronic low back pain (CLBP) may demonstrate reduced ability to perform dynamic tasks due to fear of additional pain and injury in response to the movement. The Y-balance test (YBT) is a functional and inexpensive test used with various populations. However, the reliability and validity of the YBT used for assessing dynamic balance in young adults with CLBP have not yet been examined. # Purpose To determine the inter-rater reliability of the YBT and to compare dynamic balance between young adults with CLBP and an asymptomatic group. # Study Design Reliability and validity study. # Methods Fifteen individuals with CLBP (≥ 12 weeks) and 15 age- and gender-matched asymptomatic adults completed the study. Each group consisted of 6 males and 9 females who were 21-38 years of age (27.47 ± 5.0 years). The YBT was used to measure participant's dynamic balance in the anterior (ANT), posteromedial (PM) and posterolateral (PL) reach directions. The scores for each participant were independently determined and recorded to the nearest centimeter by two raters. Both the YBT reach distances and composite scores were collected from the dominant leg of asymptomatic individuals and the involved side of participants with CLBP and were used for statistical analysis. # Results The YBT demonstrated excellent inter-rater reliability, with intraclass correlation coefficients ranging from 0.99 to 1.0 for the YBT scores of both asymptomatic and CLBP groups. The CLBP group had lower scores than those of the asymptomatic group in the reach distances of the ANT (*p* = 0.023), PM (*p* < 0.001), and PL (*p* = 0.001) directions, and the composite scores (*p* < 0.001). # Conclusions The results demonstrated excellent inter-rater reliability and validity of the YBT for assessing dynamic balance in the CLBP population. The YBT may be a useful tool for clinicians to assess dynamic balance deficits in patients with CLBP. # Level of Evidence 2b.